Pseudoaneurysm of Lumbar Artery following a Vertebral Biopsy: A Case Report - Yutaka Mifune; Masayoshi Yagi; Yasunobu Iwasaki; Minoru Doita (Case Reports in Radiology)
A 74-year-old man developed a severe low back pain and a fever. In the initial examinations, a collapse of the L5 anterosuperior vertebral body and narrowing of the L4/5 disc space were identified on radiographs, and the laboratory data showed inflammatory results. A computed tomography (CT) and a magnetic resonance imaging showed collapse of L5. A needle biopsy was performed to make a diagnosis; however, an abdominal pain and a hypotension appeared after the biopsy. An abdominal CT showed a hematoma in the retroperitoneal space, and an angiography revealed a left fourth lumbar artery pseudoaneurysm. The pseudoaneurysm was treated with transcatheter placement of microcoils. Although haemorrhagic complications following needle biopsy are very rare, patients with large amounts of vertebral destruction may have unusual anatomical positions of the lumber artery. Therefore, surgeons should be aware of the possibility of lumbar artery injury during a needle biopsy and take care of prebiopsy plans.